Primary diffuse large B-cell lymphoma of the oral cavity Linfoma difuso de grandes células B primário de boca - Bruno Correia Jham; Eliza Carla Barroso Duarte; Anacélia Mendes Fernandes; Aline Cristina Batista Rodrigues Johann; Maria Cássia Ferreira Aguiar; Ricardo Santiago Gomez; Ricardo Alves Mesquita (Sociedade Brasileira de Patologia Clínica, 2007)
Lymphomas arising within the oral cavity account for only 3.5% of all oral malignancies. Diffuse large B-cell lymphoma is a non-Hodgkin lymphoma subtype characterized by diffuse proliferation of large neoplastic B lymphoid cells. This paper reports a case of diffuse large B-cell lymphoma affecting the oral cavity of a Brazilian woman, along with its clinical, microscopical, immunohistochemical, and molecular features. Linfomas correspondem a 3,5% de todos os casos de lesões malignas de boca. O linfoma difuso de grandes células B é um subtipo de linfoma não-Hodgkin caracterizado pela proliferação difusa de células linfóides B. Este artigo relata um caso de linfoma difuso de grandes células B localizado na cavidade bucal de uma mulher brasileira, incluindo os achados clínicos, microscópicos, imuno-histoquímicos e moleculares.